Patient experiences of shared decision-making are associated with implantable cardioverter defibrillator recipients" openness to discuss device deactivation at end-of-life. (29th July 2021) - Oh, OJ; Lee, KS; Miller, J; Hammash, M; Thompson, DR; Ski, CF; Cameron, J; Moser, DK
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): In Australia, this study received funding from a faculty grand by Australian University Faculty of Health Sciences Research grant. In the United States, the study was funded by a research professor award from University of Kentucky. Background. Shared decision-making is important for ICD recipients to fully contemplate and rationally decide about ICD deactivation at end-of-life. Although discussions about device deactivation at end-of-life are recommended to be held before ICD implantation and throughout the illness trajectory, such discussions rarely occur in clinical practice. Purpose. To identify whether ICD recipients' experiences of end-of-life discussions with clinicians are associated with openness to discussing ICD deactivation at end-of-life. Methods. This cross-sectional study included 293 ICD recipients living in the United States, Australia, and South Korea (mean age 59, 22.5% female, mean ICD implantation 10 years). Hierarchical logistic regression was used to determine whether patients' experiences of shared decision-making were associated with openness to discuss device deactivation at end-of-life after controlling for relevant covariates (i.e. age, gender, ICD implantation years, ICD shock experience, general ICD experience, ICD knowledge, and concerns related to the ICD). Results. About half of the participants (57.7%) were open to discussing ICD deactivation at end-of-life with clinicians. Almost one-quarter (23.5%) had no prior experience of discussing any end-of-life issues with clinicians. Patients' past experiences of end-of-life discussions with clinicians were significantly associated with openness to discuss device deactivation at end-of-life (OR: 1.30) after adjusting for covariates. Conclusion. Our results highlight that clinicians' willingness to discuss sensitive end-of-life issues such as battery replacement and deactivation of defibrillation therapy empowers patients to actively engage in end-of-life discussions.